Peran Persepsi Dukungan Organisasional Dalam Memoderasi Hubungan Antara Kompensasi dan Kepuasan Kerja dengan Organizational Citizenship Behavior Pada Karyawan PT. Grahamas Intitirta Kuningan - Yusuf; Siddiq, Dedi Muhammad; Rudiantono, Yudi; Wardahana, Wifha Wikrama (Journal Socio Humanities Review, 2024)
This study aims to examine the relationship between compensation, job satisfaction perceived organizational support and organizational citizenship behavior. This study also observed the moderating effect of perceived organizational support on the relationship between compensation and organizational citizenship behavior and between job satisfaction and organizational citizenship behavior. The type of research used is quantitative. Respondents in this study were employees of PT. Grahamas Intitirta, and data were collected using a questionnaire. By using multiple linear regression analysis and moderating regression analysis, the results show that compensation has a positive effect on organizational citizenship behavior as well as job satisfaction has a positive influence on organizational citizenship behavior. Meanwhile, the perception of organizational support has a strengthening effect between the relationship between compensation for OCB and job satisfaction with OCB